PRACTICES OF SURVIVAL AND RESISTANCE DURING THE HOLOCAUST: INTERACTION AND MUTUAL ASSISTANCE (BASED ON INTERVIEWS COLLECTED IN THE KHERSON REGION) (Південний архів (історичні науки), 2025)
The purpose of the study is to explore individual and collective survival practices during the Holocaust in Southern Ukraine, based on oral testimonies collected as part of the Voices project of the Babyn Yar Holocaust Memorial Center (Kyiv, 2020). The research aims to reconstruct survival mechanisms, identify factors that contributed to rescue, and analyze the forms of social interaction, moral choice, and mutual assistance under the Nazi occupation regime.Methods. The study employs methods of oral history, microhistory, and the history of everyday life, combined with archival verification of testimonies. Comparative and contextual approaches are applied to identify regional features of survival strategies and to correlate personal narratives with the broader socio-political context of Nazi occupation in Ukraine. The triangulation of sources – interviews, archival materials, and museum collections – ensures the reliability and comprehensiveness of the conclusions.Results. The collected testimonies reveal diverse forms of assistance provided by relatives, neighbors, clergy, and, in some cases, even collaborators. Special attention is given to the role of non-Jewish members of “mixed” families, where mothers often devised complex strategies to save their children. Documented examples include acts of self-sacrifice for the sake of children, formal “baptisms” as a means of rescue, and sheltering Jewish children and adults in non-Jewish households. These stories demonstrate both moral courage and the ambivalence of human behavior under occupation. The testimonies also trace postwar practices of silence and the transformation of family memory, preserving the imprint of collective trauma and reflecting the influence of prosthetic memory. Conclusions. The findings confirm that survival during the Holocaust in Southern Ukraine depended not only on chance but also on networks of interpersonal relations, informal social interactions, and the moral choices of individuals. The study demonstrates that eyewitness testimonies reveal the microhistorical dimension of the Holocaust in Southern Ukraine, where individual and local experiences are embedded within a broader social context of violence, survival, and remembrance. Documenting such stories is crucial for preserving historical memory, overcoming stereotypes, and fostering intercultural dialogue.
Keywords: social interaction, family memory, everyday history, prosthetic memory, oral testimonies, microhistory, moral choice, solidarity